Using of Creamy Bioadditives in the Production of Melted Cheese - Temerbayeva, Marina; Maksim, Maksim; Gorelik, Olga; Harlap, Svetlana; Maksimiuk, Nikolai; Baitukenova, Saule; Baybalinova, Gulmira; Ermolaev, Vladimir (International Journal of Engineering and Technology, 2018)
The research identified and proposed technological parameters of production of creamy bioadditive, which is the source of probiotic microorganisms in the activated form, and intended to be used in the process cheese recipe, together with other components of milk or vegetable origin. The composition of the leaven microflora of Bifilakt-U contributes to combination of cultures of lactic acid bacteria and bifidobacteria; the concentration of protein and carbohydrates contributes to active life and growth of bifidobacteria; combination of probiotics and probiotic cultures has a positive effect on synbiotic properties of experimental products.Â Â  Â